The Kalmar Union and the Polish-Lithuanian unions (part 1) – origins and causes of establishment - Gaca, Andrzej; Bąk, Hubert (Studia Iuridica Toruniensia, 2022)
The primary purpose of the authors is to draw attention to the need for continued comparative research into the Polish-Lithuanian unions and the Kalmar Union. The study presents mainly thoughts on the origins of both unions and the early stages of the formation of those state entities. A comparative analysis has been carried out for, among others, the time of their creation together with their causes and circumstances put in the context of the stages of the social, legal-political, and institutional development of the member states (part 1). The article also outlines the later history and transformations of these unions: both their factual and legal character, as well as the regulations of their functioning and consequences (part 2). These questions are presented mainly in a comparative way, with consideration of differences and similarities between the two unions. The authors bring out the problems of a political, social, and economic nature, together with the dynastic policy of the united states; next, they describe similarities between the regulations of the unions regarding the order of succession to the throne. The subject of a synthetic comparison is also the later history of the two unions after they formally ended and their impact on the historical development of both Poland and Lithuania and the northern states. Still, one of the most important issues seems to be the answer to the question why both of the unions wasted their considerable political and military potential for joint action and new opportunities to achieve common political aims in northern and eastern Europe. It would be worthwhile to compare their durability and influence on the future of their member states. One of the leading research proposals based on the attempts made so far is to compare the subsequent stages, transformations, and results, both direct and long-lasting, of the analyzed unions of the states. The adoption of such a broad research perspective which is only outlined here, and then an attempt at a more comprehensive synthesis requires, in the authors opinion, the collective efforts of many scholars, and especially the international cooperation of historians specializing in Polish-Lithuanian and Swedish-Danish-Norwegian relations as well as the history of the Teutonic Order and the Hanseatic League.